Psychological Aspects of Special Public Service Personnel - Battulga, Ankhtuya (Advances in Social Sciences Research Journal, 2025)
The purpose of our study is to conduct a comparative analysis of the current level of selected psychological issues among public servants in special government institutions, using available sources and data that identify and document these issues. The research examines key psychological aspects affecting special public service personnel, including occupational stress, emotional regulation, job-related pressure, and professional well-being. Drawing on comparative data from prior studies, institutional reports, and empirical findings, the study analyzes similarities and differences in psychological conditions across institutional and functional contexts. The findings highlight that the unique nature of special public service—characterized by high responsibility, strict discipline, and exposure to risk—significantly influences psychological health and job performance. Our study contributes to the literature on public service psychology by providing evidence-based insights that may inform institutional policy, psychological support mechanisms, and human resource management strategies within special government organizations.